Interactive GUIs and 3D Visualization in Computational Mathematics Education: A Systematic Literature Review - Syaharuddin, Syaharuddin; Abdillah, Abdillah; Mehmood, Saba; Raza, Wasim; Sahraini, Alfiana; Fadugba, Sunday Emmanuel (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Graphical User Interfaces (GUIs) and 3D visualization can support computational mathematics learning by making abstract, spatial, and dynamic concepts more accessible. However, evidence concerning their pedagogical applications, reported outcomes, and implementation challenges remains fragmented across technologies and educational contexts. This systematic literature review identifies, classifies, and synthesizes research on GUI- and 3D-supported computational mathematics education. Open-access publications written in English or Indonesian and indexed in Scopus, the Directory of Open Access Journals, and Google Scholar between 2015 and 2025 were examined using a PRISMA-informed selection process. Of the 28,563 records initially identified, 1,123 were retained for bibliometric and keyword co-occurrence analysis, while 31 studies met the full eligibility criteria and were included in the qualitative synthesis. The included studies were analyzed through thematic coding, cross-study comparison, and narrative synthesis. Bibliometric mapping identified four major clusters: technology-supported learning environments; visualization, GUI, and user interaction; simulation and advanced computational methods; and datasets, images, and predictive models. Across the included studies, GUI and 3D visualization were generally associated with reported improvements in conceptual understanding, learning motivation, engagement, and interaction with mathematical representations. Nevertheless, their educational value depended on usability, instructional scaffolding, curriculum alignment, teacher readiness, and technological accessibility. The findings provide design-oriented guidance for educators and developers and highlight the need for rigorous research in non-geometry domains, standardized evaluation methods, and integrated pedagogical frameworks for computational mathematics education.